Temporal Variation of Growth and Condition Index of Clams (Corbicula fluminea) in The Lahumbuti River, Konawe, Southeast Sulawesi - Bahtiar Bahtiar; Latifa Fekri; Muh. Ardin La Musa; Ulfi Damayanti; Muh. Fajar Purnama (Masyarakat Moluska Indonesia, 2023)
Corbicula fluminea in the Lahumbuti River have unknown growth, condition index and meat weight ratio. This study aims to determine the temporal variation of growth and condition index of clams in the Lahumbuti River, Konawe, Southeast Sulawesi. This research was conducted in August 2021-July 2022 on the Lahumbuti River, Konawe, Southeast Sulawesi. The clams were taken by purposive random sampling using a shovel in a 1x1 m2 quadrant. Furthermore, the width of the clam and the weight of wet meat sample was measured, using a caliper (0.5 mm) and a digital scale (0.01 g) at the Laboratory of faculty of Fisheries and Marine Science, Halu Oleo University. Furthermore, the clams were dried using an oven at 60oC for 48 hours and weighed using an analytical balance (0.0001 g). Data were analyzed descriptively quantitatively using a standard formula. The results showed that the average b value was 2.15 and the coefficient of determination (R2) was 5.18. The t test showed that mussels were in a negative allometric condition. The value of b varies temporally. The lowest b value was in October (1.60) and experienced an increase and reached a peak in February (3.0) with an R2 value ranging from 83.18 to 93.24. The condition factor was at a mean value of 2.54 ± 1.08 which ranged from 1.60 ± 0.54 to 3.58 ± 1.12. The highest condition index occurred in November (3.58) and the lowest occurred in April (1.60). In general, the clam condition index was in the lean category.